Difficulties physical therapy students have with orthotics during clinical practice : An analysis using text mining - 山本 裕晃; 善明 雄太; 宮原 拓也 (Journal of Assistive Technology in Physical Therapy, 2024)
Purpose : To identify orthotic difficulties in clinical practice. By identifying points to consider for orthotics, we aimed to utilize this information for both on — campus and practical training education.Participants and Methods : The subjects were 20 physical therapy students from a vocational school who had completed their clinical training. A survey on orthotic difficulties was conducted using an open — ended questionnaire.Results : In the clinical practice, we were able to confirm the items that cause difficulties regarding orthotics. It was also confirmed that orthotic involvement was low.Conclusion : In order to ensure that physiotherapy students do not experience any difficulties, training schools need to make specific requests to the clinical practice educators regarding the content, such as visits and experiences related to orthosis, depending on the physiotherapy students’ abilities.